Comparative Quality Evaluation of Universities' Institutional Repositories of Peru - Fernando Blanco-Olea (JLIS.it, 2021)
This article evaluates and compare the quality level of the top 10 Peruvian universities’ institutional repositories by using the RECOLECTA Evaluation Guide for Research Institutional Repositories. The data was collected on December 2020 from various sources including the repositories’ interfaces, the repositories’ managers, the OAI-PMH Validator, among others. The results reveal that most of the repositories perform a high-level criteria fulfillment in 4 evaluation areas: “Policies”, “Metadata”, “Interoperability”, and “Security, authenticity and integrity of data”, a mid-level criteria fullfillment in the Legal aspects area, and a low-level criteria fullfillment in the “Visibility” and the “Logs and statistics” areas. Lastly, no correlation was found between the repositories’ quality level and their universities’ position in the SUNEDU’s Best Peruvian Universities ranking.